Improving the Design of Diamond Wheel for High-Speed Grinding - Mamalis, A. G.; Grabchenko, A. I.; Fedorovich, V. A.; Romashov, D. V. (Nova Science Publishers, Inc., 2016)
Grinding at high speeds is a complex process requiring specific tools for successful use. Rotational stresses during high-speed grinding can lead to failure if the wheel is not correctly designed. These results are extremely difficult to be obtained during a large number of field experiments due to the high cost of testing equipment. So, the article describes ways of improving the integrity of the body of the diamond grinding wheel for high-speed regimes using analytical approaches and finite element method.
Keywords: finite element method; destructive stress; design; construction